Stability Studies of the Dilution Series of Different Antibiotic Stock Solutions in Culture Medium Incubated at 37 °C - Ádám Kerek; Bence G. Ecsedi; Ábel Szabó; Zoltán Szimrók; Bianka Paliczné Kustán; Ákos Jerzsele; Gábor Nagy (MDPI AG, 2024)
The long-term stability of antibiotics in culture media remains underexplored in scientific literature. This study evaluated the stability of eight distinct antibiotic stock solutions-amoxicillin, cefotaxime, neomycin, oxytetracycline, florfenicol, enrofloxacin, colistin, and potentiated sulfonamide-and their 10-fold dilution series in tryptone soy broth (TSB) at 37 °C, over 12 days. Samples were collected immediately after preparation and on days 1, 2, 5, 7, 9, and 12, with active substance concentrations measured using ultra-high-performance liquid chromatography (UHPLC) coupled with mass spectrometry. The results indicated that among the ultrapure water stock solutions, neomycin, florfenicol, and potentiated sulfonamide maintained stability (>95%). Within the culture medium, florfenicol showed consistent stability (100%) throughout the study, potentiated sulfonamide experienced minor degradation (>85%), and neomycin underwent significant degradation. Amoxicillin, oxytetracycline, and colistin displayed considerable degradation in both solution types but were more stable in ultrapure water solutions. The stability of cefotaxime and enrofloxacin in ultrapure water solutions and in the medium was very similar when compared; however, 3.6% of the former and 88.7% of the latter remained detectable by day 12. These findings are crucial for minimum inhibitory concentration (MIC) assessments, especially in minimum bactericidal concentration (MBC) studies, and in experiments concerning long-term evolution and co-selection. This study underscores the necessity of stability assessments in culture media to validate future experimental outcomes.